The The Influence of Millenial Leadership and Job Transfer Patterns on Organizational Culture and Employee Performance at KPP Pratama Jakarta Tanah Abang Two and KPP Pratama Jakarta Tanah Abang Three - Issabella Manalu; Nur Hastuty Kesumo Wardhani; Murtanto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Abstract Millennial leadership and job transfer patterns are considered important factors in strengthening organizational culture and improving employee performance. This study employed a quantitative approach using a survey method. The research population consisted of all employees of KPP Pratama Jakarta Tanah Abang Two and KPP Pratama Jakarta Tanah Abang Three, with a sample of 114 respondents. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that Millennial Leadership has a positive and significant effect on Organizational Culture, with a path coefficient of 0.448, a t-statistic value of 6.025, and a p-value of 0.000. Similarly, Job Transfer Patterns also have a positive and significant effect on Organizational Culture, with a path coefficient of 0.413, a t-statistic value of 5.156, and a p-value of 0.000. Millennial Leadership does not have a significant effect on Employee Performance, as indicated by a path coefficient of 0.141, a t-statistic value of 1.471, and a p-value of 0.142. In contrast, Job Transfer Patterns have a positive and significant effect on Employee Performance, with a path coefficient of 0.151, a t-statistic value of 1.997, and a p-value of 0.046. Furthermore, Organizational Culture has a positive and significant effect on Employee Performance, with a path coefficient of 0.648, a t-statistic value of 5.712, and a p-value of 0.000. Organizational Culture is also proven to mediate the relationship between Millennial Leadership and Employee Performance (β = 0.290; t = 3.824; p = 0.000) as well as the relationship between Job Transfer Patterns and Employee Performance (β = 0.268; t = 3.685; p = 0.000). These findings indicate that improving employee performance within KPP Pratama is influenced not only by leadership quality and the implementation of job transfer policies but also, and more importantly, by the strength of organizational culture in internalizing the values of integrity, professionalism, synergy, service excellence, and continuous improvement.